Highly Sensitive Simultaneous Measurement of Steroid Hormone in Human Serum by Liquid Chromatography-electrospray Ionization Tandem Mass Spectrometry - Van Khanh, Nguyen; Thanh Hai, Nguyen; Thi Dieu Thuy, Nguyen; Kido, Teruhiko; F. Nakayama, Shoji; Isobe, Tomohiko; Okuyama, Mitunobu Okuyama; Honma, Seijiro (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 38 No 1, 2022)
A high sensitive simultaneous determination method of nine steroid hormones including Estrone (E1), estradiol (E2), testosterone (T), dihydrotestosterone (DHT), 17-hydroxyprogesterone (17OH-P4), androstenedione (AN), progesterone (P4), dehydroepiandrosterone (DHEA), and cortisol by liquid chromatography-electrospray ionization tandem mass spectrometry (LC-ESI-MS/MS) was established in a positive mode using recently developed picolinyl derivatization. Steroid hormones were derived with picolinic acid and 2-methyl-6-nitrobenzoic anhydride, then purified by solid-phase extraction with InterSep SI cartridge. The LC-ESI-MS/MS method enhanced the specificity and sensitivity for E1, E2, T, DHT, DHEA, and cortisol. The method validation indicated that the limits of quantification for E1, E2, T, DHT, 17OH-P4, AN, P4, DHEA, and cortisol were 1, 1, 1, 2, 2, 2, 2, 20, and 100 pg/tube, respectively with acceptable accuracy and precision within ± 15%. The present method was applied to the measurement of nine steroid hormones in children’s serums with high reliability and reproducibility. Keywords: LC-ESI-MS/MS, steroid hormone, picolinyl derivatization, human serum, solid-phase extraction. References [1] A. R. Vasconcelos, J. V. C. Costa, C .H. Mazucanti, C. Scavone, E. M. Kawamoto, The Role of Steroid Hormones in the Modulation of Neuroinflammation by Dietary Interventions, Front Endocrinol (Lausanne), Vol. 7, 2016, pp. 1-14, https://doi.org/10.3389/fendo.2016.00009. [2] D. French, Advances in Bioanalytical Techniques to Measure Steroid Hormones in Serum, Bioanalysis, Vol. 8, No. 11, 2016, pp. 1203-1219, https://doi.org/10.4155/bio-2015-0025. [3] R. Schoenheimer, D. Rittenberg, Deuterium as an Indicator in the Study of Intermediary Metabolism, Science, Vol. 82, No. 2120, 1935, pp. 156-157, https://doi.org/ 10.1126/science.82.2120.156. [4] P. Eneroth, K. Hellstroem, R. Ryhage, Idenfication and Quatification of Neutral Fecal Steroids by Gas-liquid Chromatography and Mass Spectrometry: Studies of Human Excretion during Two Dietary Regimens, J Lipid Res, Vol. 5, 1964, pp. 245-262. [5] R. Rhyage, Use of a Mass Spectrometer as a Detector and Analyzer for Effluent Emerging from High Temperature Gas Liquid Chromatography Columns, Vol. 36, No.4, 1964, pp. 759-764, https://doi.org/10.1021/ac60210a019 36. [6] G. E. Abraham, Solid-phase Radioimmunoassay of Estradiol-17 Beta, J Clin Endocrinol Metab, Vol. 29, No. 6, 1969, pp. 866-870, https://doi.org/10.1210/jcem-29-6-866. [7] M. Zendjabil, Z. Chellouai, O. Abbou, Role of Mass Spectrometry in Steroid Assays, Ann Endocrinol (Paris), Vol. 77, No. 1, 2016, pp. 43-48, https://doi.org/10.1016/j.ando.2016.01.004. [8] C. Shackleton, Clinical Steroid Mass Spectrometry: a 45-year History Culminating in HPLC-MS/MS Becoming an Essential Tool for Patient Diagnosis, J Steroid Biochem Mol Biol, Vol. 121, No. 3-5, 2010, pp. 481-490, https://doi.org/10.1016/j.jsbmb.2010.02.017. [9] M. Závada, K. Šafarčik, O. Topolčan, Some Problems of Radioimmunoassay Control, Journal of Radioanalytical Chemistry, Vol. 46, No. 1, 1978, pp. 57-66. [10] M. Z. Nouri, K. J. Kroll, M. Webb, N. D. Denslow, Quantification of Steroid Hormones in Low Volume Plasma and Tissue Homogenates of Fish using LC-MS/MS, Gen Comp Endocrinol, Vol. 296, pp. 1-15, https://doi.org/10.1016/j.ygcen.2020.113543. [11] N. Kadian, K. S. R. Raju, M. Rashid, M. Y. Malik, I. Taneja, M. Wahajuddin, Comparative Assessment of Bioanalytical Method Validation Guidelines for Pharmaceutical Industry, J Pharm Biomed Anal, Vol. 126, 2016, pp. 83-97, https://doi.org/10.1016/j.jpba.2016.03.052. [12] Food and Drug Administration, Bioanalytical Method Validation Guidance for Industry, USA, 2018, pp. 1-44. [13] European Medicines Agency, Guideline on Bioanalytical Method Validation, Italy, 2012, pp. 1-23. [14] T. Higashi, S. Ogawa, Chemical Derivatization for Enhancing Sensitivity during LC/ESI-MS/MS Quantification of Steroids in Biological Samples: a Review, J Steroid Biochem Mol Biol, Vol. 162, 2016, pp. 57-69, https://doi.org/10.1016/j.jsbmb.2015.10.003. [15] L. Aksglaede, A. Juul, H. Leffers, N. E. Skakkebaek, A. M. Andersson, The Sensitivity of the Child to Sex Steroids: Possible Impact of Exogenous Estrogens, Hum Reprod Update, Vol. 12, No. 4, 2006, pp. 341-349, https://doi.org/10.1093/humupd/dml018. [16] E. Benyi, L. Sävendahl, The Physiology of Childhood Growth: Hormonal Regulation, Horm Res Paediatr, Vol. 88, No. 1, 2017, pp. 6-14, https://doi.org/10.1159/000471876. [17] J. Cui, Y. Shen, R. Li, Estrogen Synthesis and Signaling Pathways during Aging: From Periphery to Brain, Trends in Molecular Medicine, Vol. 19, No. 3, 2013, pp. 197-209, https://doi.org/10.1016/j.molmed.2012.12.007. [18] G. Jasienska, R. G. Bribiescas, A. S. Furberg, S. Helle, A. N. L. Mora, Human Reproduction and Health: an Evolutionary Perspective, Lancet, Vol. 390, No. 10093, 2017, pp. 510-520, https://doi.org/10.1016/S0140-6736(17)30573-1. [19] A. E. Kulle, F. G. Riepe, D. Melchior, O. Hiort, P. M. Holterhus, A Novel Ultrapressure Liquid Chromatography tandem Mass Spectrometry Method for the Simultaneous Determination of Androstenedione, Testosterone, and Dihydrotestosterone in Pediatric Blood Samples: Age- and Sex-specific Reference Data, J Clin Endocrinol Metab, Vol. 95, No. 5, 2010, pp. 2399-409, https://doi.org/10.1210/jc.2009-1670. [20] A. L. Southren, S. Tochimoto, N. C. Carmody, K. Isurugi, Plasma Production Rates of Testosterone in Normal Adult Men and Women and in Patients with the Syndrome of Feminizing Testes, The Journal of Clinical Endocrinology & Metabolism, Vol. 25, No. 11, 1965, pp. 1441-1450, https://doi.org/10.1210/jcem-25-11-1441. [21] R. S. Swerdloff, R. E. Dudley, S. T. Page, C. Wang, W. A. Salameh, Dihydrotestosterone: Biochemistry, Physiology, and Clinical Implications of Elevated Blood Levels, Endocr Rev, Vol. 38, No. 3, 2017, pp. 220-254, https://doi.org/10.1210/er.2016-1067. [22] J. P. Mulhall, L. W. Trost, R. E. Brannigan,E. G. Kurtz, J. B. Redmon, K. A. Chiles, D. J. Lightner, M. M. Miner, M. H. Murad, C. J. Nelson, E. A. Platz, L. V. Ramanathan, R. W. Lewis, Evaluation and Management of Testosterone Deficiency: AUA Guideline, J Urol, Vol. 200,  No. 2, 2018, pp. 423-432, https://doi.org/10.1016/j.juro.2018.03.115. [23] H. Frederiksen, T. H. Johannsen, S. E. Andersen,J. Albrethsen, S. K. Landersoe, J. H. Petersen, A. N. Andersen, E. T. Vestergaard, M. E. Schorring, A. Linneberg, K. M. Main, A. M. Andersson, A. Juul, Sex-specific Estrogen Levels and Reference Intervals from Infancy to Late Adulthood Determined by LC-MS/MS, J Clin Endocrinol Metab, Vol. 105, No. 3, 2020, pp. 754-68, https://doi.org/10.1210/clinem/dgz196. [24] K. Yamashita, M. Okuyama, R. Nakagawa, S. Honma, F. Satoh, R. Morimoto, S. Ito, M. Takahashi, M. Numazawa, Development of Sensitive Derivatization Method for Aldosterone in Liquid Chromatography–electrospray Ionization Tandem Mass Spectrometry of Corticosteroids, Journal of Chromatography A, Vol. 1200, No. 2, 2008, pp. 114-121, https://doi.org/10.1016/j.chroma.2008.05.034. [25] K. Yamashita, Y. Miyashiro, H. Maekubo, M. Okuyama, S. Honma, M. Takahashi,M. Numazawa, Development of Highly Sensitive Quantification Method for Testosterone and Dihydrotestosterone in Human Serum and Prostate Tissue by Liquid Chromatography-electrospray Ionization tandem Mass Spectrometry, Steroids, Vol. 74, No. 12, 2009, pp. 920-926, https://doi.org/10.1016/j.steroids.2009.06.007.